O sistema brasileiro de repressão ao assédio moral no ambiente de trabalho - Galvão, Vivianny Kelly (2010)
Mobbing has found space in the modern work relationships. The change of rhythm, the high competitiveness and the fear of unemployment are factors which contextualize these work environments. The psicoterror, Marie-France Hirigoyen’s denomination, arises from actions like gestures, verbal or physical aggressions, as well as omissions, isolating the victim and leaving her without the essential information to development his/hers activities. The mobbing’s characterization and punishment are surrounded by a high degree of subjectivity because of its forms of aggression that usually leaves no traces. Therefore, it’s necessary to study and understand the forms of repression the psicoterror, considering the concept of a supranational right, the moral integrity of workers. Means that recognition occurs at the international level, above the states orders. Besides affecting the rules of reception of international treaties on human rights, the supranational nature of the workers’ rights ratified the discourse of relativized sovereignty and imposes to the internal organization the creation of actions for its protection. The actions can be preventatives, through public politics, community action, standards of work’s organization, lectures, or repressives, based on the subsystem of the offender’s responsibility. The case studies revealed that, in Brazil and other countries, violence against workers has proved to be one of the most serious human rights violations.